2023
DOI: 10.3390/nu15040938
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet and Ultra-Processed Foods Consumption in a Group of Italian Patients with Celiac Disease

Abstract: Evidence on the consumption of ultra-processed foods (UPF) in adults with celiac disease (CD) and its impact on Mediterranean Diet (MD) adherence is still limited. Our aim was to determine UPF consumption and its relationship with MD adherence in a group of adults, according to the presence of CD. This case-control study included 103 adults with CD and 312 without CD. UPF intake was assessed using the NOVA Food Frequency Questionnaire (NFFQ), while MD adherence was assessed using the Medi-Lite score. UPF repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 31 publications
1
30
0
1
Order By: Relevance
“…In this regard, Dinu et al studied UPF consumption in a group of Italian adults, observing a significant inverse association between adherence to the Mediterranean diet (as assessed by the Medi-Lite score) and the percentage of UPF in the diet [ 3 ]. Similar results were found by Tristan Asensi et al who observed an inverse trend between UPF consumption and adherence to the Mediterranean diet in adults with celiac disease [ 4 ]. The association between UPF consumption and diet was also considered by Nansel and colleagues, who found that UPF intake during pregnancy and postpartum was inversely related to 8 of 13 component scores of the 2015 Healthy Eating Index [ 5 ].…”
supporting
confidence: 88%
“…In this regard, Dinu et al studied UPF consumption in a group of Italian adults, observing a significant inverse association between adherence to the Mediterranean diet (as assessed by the Medi-Lite score) and the percentage of UPF in the diet [ 3 ]. Similar results were found by Tristan Asensi et al who observed an inverse trend between UPF consumption and adherence to the Mediterranean diet in adults with celiac disease [ 4 ]. The association between UPF consumption and diet was also considered by Nansel and colleagues, who found that UPF intake during pregnancy and postpartum was inversely related to 8 of 13 component scores of the 2015 Healthy Eating Index [ 5 ].…”
supporting
confidence: 88%
“…Neuroinflammation is characterized by hyperactivation of peripheral glia, including Schwann cells, satellite glial cells in the posterior horn of the spinal cord, and trigeminal nerve ganglia, and central glia, including microglia, astrocytes, and oligodendrocytes in the spinal cord and brain [82]. A diet high in processed foods and saturated and trans fats may contribute to the promotion of low-grade inflammation and increase the risk of the development of non-communicable diseases, including neurological disorders [84].…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Participants with higher UPF intake had higher leukocyte counts which was consistent with a previous hypothesis that UPF intake is associated with chronic inflammation. 46 The literature suggests that inflammation involves a complex network of interactions among various immune-related factors, including C-reactive pro-teins and lymphocytes, which may in turn induce ongoing respiratory tissue damage and injury. 47 UPF consumption was also linked to increased levels of glucose and lipid metabolism.…”
Section: Papermentioning
confidence: 99%